SAT0613 Sonoelastography is a Novel Imaging Biomarker in Spondyloarthropathy: A Pilot Study. (9th June 2015) - Sahbudin, I.; Peall, A.; Filer, A.
Abstract : Background: Sono-elastography (SE) is a novel ultrasound application that quantifies the tissue elasticity (ie the degree of tissue stiffness) within an anatomical structure. It provides a different aspect of biomechanical tissue information that can complement Grey-Scale Ultrasound (GSUS) and Power Doppler Ultrasound (PDUS) findings. At present, the value of SE in the detection of clinical enthesitis in Spondyloarthropathy (SpA) is yet to be assessed. Objectives: The aim of this pilot study was to explore the diagnostic ability of SE compared to GSUS and PDUS in the detection of clinical enthesitis in SpA Methods: A total of 40 enthesial sites of patients with physician-diagnosed SpA were included in the analysis. Bilateral proximal plantar fascia, distal Achilles tendon, distal and proximal patellar tendon insertion and distal quadriceps tendon were systematically scanned with the same Aplio-400 ™ Diagnostic Ultrasound System (Toshiba Medical Systems Corporation; multi-frequency transducer 7-18Hz) in GSUS, PDUS and real-time sonoelastography imaging mode. SE grading was based on differential tissue stiffness; blue-green (hard) =0, green-yellow (intermediate) =1, yellow-red (soft) =2, red (very soft) =3. GSUS and PDUS were graded based on the validated Madrid Sonographic Enthesis Index (MASEI) scoring system [i.e. calcification, power Doppler enhancement, erosions, tendon structure, tendon thickness and bursa was scored on a semi-quantitative scale of 0-3]. Results: SE grading strongly correlated with PDUS grading (rS =0.852, p<0.01), and combined GSUS/PDUS gradings (rS =0.716, p<0.01). Conclusions: This is the first study to compare the diagnostic ability of SE with conventional US for the detection clinical enthesitis in SpA. SE is a promising new imaging biomarker in SpA; further work is required to standardise the grading system, image acquisition and reliability of this novel US application. Disclosure of Interest: None declared